Recent updates on anticancer mechanisms of polyphenols - Sharma, Eshita; Attri, Dharam Chand; Sati, Priyanka; Dhyani, Praveen; Szopa, Agnieszka; Sharifi-Rad, Javad; Hano, Christophe; Calina, Daniela; Cho, William C. (Frontiers in Cell and Developmental Biology, 2022)
In today’s scenario, when cancer cases are increasing rapidly, anticancer herbal compounds become imperative. Studies on the molecular mechanisms of action of polyphenols published in specialized databases such as Web of Science, Pubmed/Medline, Google Scholar, and Science Direct were used as sources of information for this review. Natural polyphenols provide established efficacy against chemically induced tumor growth with fewer side effects. They can sensitize cells to various therapies and increase the effectiveness of biotherapy. Further pharmacological translational research and clinical trials are needed to evaluate theirs in vivo efficacy, possible side effects and toxicity. Polyphenols can be used to design a potential treatment in conjunction with existing cancer drug regimens such as chemotherapy and radiotherapy.